Avalia????o da rela????o entre a virtualidade de equipes e o desempenho operacional de projetos: uma an??lise quantitativa. - Vargas Neto, Durval Mescua (2014)
The problems of large urban centers such as manning of collective transport, traffic congestion and environmental pollution issues, together with the technological development of communication and information corroborate to viability of teleworking modality also known as home office. This contemporary form of work into the context of project management assists companies achieve their strategies regarding the requirements of anmarket increasingly competitive.The disseminating virtual project teams is mainly moved by economic gains that occur in reducing the physical space of the company, because real estate is expensive, but also for the economy displacement from home to the company beyond the time lost in traffic.This dissertation has its central theme, evaluate the relationship between virtuality teams and operational performance of projects. Its main purpose is to measure quantitatively the influence of degree of virtuality teams in operating performance of consulting projects property security. The methodological procedure in this investigation was quasi-experimental research the type ex post facto. The database composed of 85 projects, was collected in an international firm of consulting andservices risk management business, which uses virtual project teams.The results demonstrate that there is a dependency relationship between virtuality of teams and schedule and cost performanceof the projects. When the project is less complex, the odds of success of the operational cost is higher, however it does not confirm to the odds of success of the operational schedule.The conclusion of the research reveals that the degree of virtuality teams has statistically positive impact on schedule and costperformance of the projects. Additionally it was not possible to prove statistically that the complexity of the projects impacts the relationship between virtuality teams and the schedule performance, but confirm the influence of project complexity in the relationship between virtuality teams and cost performance.